Simple coded identification references of harvesting time for oil palm fruits - Nik Mahadi, Nik Izzat Hazwan; Adam, Mohd Bakri; Silalahi, Divo Dharma (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
The ripeness grading of oil palm fresh fruits is very important. The conventional practice in the oil palm factories is to grade oil palm manually by sending some samples to laboratory. This method takes two weeks to get results and may subject to dispute. An automated grading system for oil palm fresh fruits using Red, Green and Blue colors system is used as an alternative way. This grading system is developed to distinguish between the different categories of oil palm fresh fruits. The maturity or color ripening index is based on different color intensity. Hence, a coded method with sunflower plots will be introduced to give a better inference on the colors in identifying harvesting of oil palm fresh fruits.